2015
DOI: 10.1021/acs.inorgchem.5b00603
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Stable Trigonal Bipyramidal Copper(III) Complexes Equipped with an Exchangeable Axial Ligand

Abstract: A stable trigonal bipyramidal copper(III) complex, [PPN][Cu((TMS)PS3)Cl] (1, wherein PPN represents bis(triphenylphosphine)iminium), was synthesized from CuCl2/PPNCl via intramolecular copper(II) disproportionation. Under ambient conditions, the axial chloride of 1 is exchangeable in solution thus making 1 serve as an intermediate to prepare trigonal bipyramidal copper(III) derivatives, e.g., [PPN][Cu((TMS)PS3)(N3)] (2) and [Cu((TMS)PS3)(DABCO)] (3). Diamagnetic complexes 1-3 were fully characterized by X-ray … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Compound 2a displayed a 1s → 3d pre-edge transition centered at 8978.1 eV (Figure ), while 2b had an equivalent peak at 8979.4 eV, approximately 1.3 eV higher in energy (Figure S10). These pre-edge transition energies fall within the expected range for Cu II and Cu III complexes, respectively. DuBois et al showed a shift of 1.0–2.0 eV for Cu II to Cu III pairs and demonstrated that this was the only reliable predictor of oxidation state for Cu XANES .…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…Compound 2a displayed a 1s → 3d pre-edge transition centered at 8978.1 eV (Figure ), while 2b had an equivalent peak at 8979.4 eV, approximately 1.3 eV higher in energy (Figure S10). These pre-edge transition energies fall within the expected range for Cu II and Cu III complexes, respectively. DuBois et al showed a shift of 1.0–2.0 eV for Cu II to Cu III pairs and demonstrated that this was the only reliable predictor of oxidation state for Cu XANES .…”
Section: Resultssupporting
confidence: 53%
“…The pre-edge features have the same normalized intensity for both 2a and 2b , suggesting that there has not been a change in geometry or coordination number. Altering the geometry and so the degree of 3d and 4p mixing would change the intensity of this feature. , The 1.3 eV blue shift suggested an integer change in the oxidation state of the metal (thus Cu II to Cu III ). …”
Section: Resultsmentioning
confidence: 99%
“…L CuF is, to the best of our knowledge, the first structurally characterized, discrete copper­(III) fluoride complex and features the shortest Cu–F distance (1.755(3) Å) reported in the Cambridge Structural Database. Furthermore, L CuCl and L CuBr feature shorter Cu–Cl (2.1085(8) Å) and Cu–Br (2.2562(4) Å) bonds than previously reported five-coordinate copper­(III) halide complexes (Cl: 2.2011(18)–2.468(1) Å; Br: 2.3842(5)–2.600(1) Å). , …”
Section: Resultsmentioning
confidence: 66%
“…However, given the fidelity between experiment and theory showcased earlier in the prediction of Cu 3d contributions to the LUMOs/SOMOs of formally Cu III complexes, we have extended our calculations to explore the generality of ligand field inversion in a diverse sampling of other formally Cu III complexes (Figure ). ,,, The calculated LUMOs for each species are shown in Figure along with the corresponding Löwdin orbital compositions. Again, regardless of supporting ligand and geometry, our calculations show that all but one species considered ([CuF 6 ] 3– ) possess LUMOs with <50% Cu 3d-character.…”
Section: Resultsmentioning
confidence: 99%